WAYS TO EFFECTIVELY ORGANIZE THE PARTICIPATION OF INSTITUTIONAL INVESTORS IN THE SECURITY MARKET (Conferencea, 2023)
In the effective implementation of economic reforms in our country, it is important to organize innovative development, create a healthy investment environment, and attract institutional investors to the economy. Therefore, it is important to attract institutional investors to the capital market of our country, to expand their participation, and to develop the capital market.Inspite of the role of the capital market is large in developed countries, it should be noted that the importance of the capital market is growing in developing countries as well. Institutional investors play an important role in capital market development in many developed and developing countries, and institutional investors are seen as a source of financing for the corporate sector. In the development of the capital market, tasks such as effectively establishing the activities of institutional investors, creating the necessary conditions for their free operation, increasing investment attractiveness, and ensuring the openness and reliability of information are given priority.